Protective Effect of Chokeberry (Aronia melanocarpa L.) Extract against Cadmium Impact on the Biomechanical Properties of the Femur: A Study in a Rat Model of Low and Moderate Lifetime Women Exposure to This Heavy Metal - Brzóska, Małgorzata M. (Nutrients, 2017)
The hypothesis that the consumption of Aronia melanocarpa berries (chokeberries) extract, recently reported by us to improve bone metabolism in female rats at low-level and moderate chronic exposure to cadmium (1 and 5 mg Cd/kg diet for up to 24 months), may increase the bone resistance to fracture was investigated. Biomechanical properties of the neck (bending test with vertical head loading) and diaphysis (three-point bending test) of the femur of rats administered 0.1% aqueous chokeberry extract (65.74% of polyphenols) or/and Cd in the diet (1 and 5 mg Cd/kg) for 3, 10, 17, and 24 months were evaluated. Moreover, procollagen I was assayed in the bone tissue. The low-level and moderate exposure to Cd decreased the procollagen I concentration in the bone tissue and weakened the biomechanical properties of the femoral neck and diaphysis. Chokeberry extract administration under the exposure to Cd improved the bone collagen biosynthesis and femur biomechanical properties. The results allow for the conclusion that the consumption of chokeberry products under exposure to Cd may improve the bone biomechanical properties and protect from fracture. This study provides support for Aronia melanocarpa berries being a promising natural agent for skeletal protection under low-level and moderate chronic exposure to Cd.